One-pot access to sulfonylated naphthalenediols/hydroquinones from naphthols/phenols with sodium sulfinates in an aqueous medium. (17th December 2020) - Meng, Lingxin; Zhang, Ruike; Guan, Yuqiu; Chen, Tian; Ding, Zhiqiang; Wang, Gongshu; Reheman, Aikebaier; Chen, Zhangpei; Hu, Jianshe
Abstract : A metal-free method towards sulfonylated hydroquinones/naphthalenediols under an ambient atmosphere has been developed with up to 97% yield. Abstract : A one-pot method towards sulfonylated hydroquinones/naphthalenediols in an aqueous medium has been developed with up to 97% yield. The whole reaction requiring no transition-metal catalysts could proceed smoothly with hypervalent iodine compounds as the oxidant. Both naphthols and phenols were viable with inexpensive and readily available sodium sulfinates as the sulfonylation reagents under an ambient atmosphere. This procedure is scalable, and the products could be easily obtained without column chromatography isolation.